Supporting Lactation Within an Academic Anesthesia Department: Obstacles and Opportunities. Issue 1 (24th March 2021) - Titler, S.S.; Pearson, A.C.S.
Abstract : ( Anesth Analg . 2020;131:1304–1307) There is a growing number of women in academic anesthesiology, many of whom are in their prime reproductive years. Following maternity leave, many would like to continue breastfeeding, but there are a number of barriers. This report identifies common barriers to lactation in the workplace, solutions for removing these barriers, and requirements for lactation spaces in the workplace.